Perubahan Kadar Komponen Kimia Bambu Kuning akibat Modifikasi Steam dan Pembilasan (Change of Chemical Component Content in Kuning Bamboo due to Steam and Rinsing Modification) - Muhammad I Maulana; Abi K Arif; Deded S Nawawi; Nyoman J Wistara; Siti Nikmatin; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
Bamboo is a forest product that has potential as substitution of wood for the raw material of any products of forest products processing. Oriented Strand Board (OSB) made from bamboo is more superior compared to the wood one in physical and mechanical properties. Steam and rinsing treatments can improve the OSB properties that occur due to changes in the chemical components of bamboo, but research on the effect of the treatment has not been done for kuning bamboo. The objective of this reseach were to identify the changes of chemical components content in kuning bamboo (Bambusa vulgaris var. striata.) due to steam, steam with distillation water rinsing and steam with 1% NaOH rinsing treatments. The chemical component of bamboo was analyzed according to Technical Association of the Pulp and Paper Industry (TAPPI) standards. The results showed that alpha-cellulose and lignin contents were relatively stable. In addition, hollocellulose, hemicellulose and extractives decreased, while the pH value was increased by treatments. The decreased of hemicellulose and extractive substances, as well as increased pH values can improve the quality of OSB produced.